Respuesta :

The given function is f(a)=[tex]-2a^{2}-5a+4.[/tex])

The question is asking us to find f(-3)

To find f(-3) we replace a by -3.

f(-3)=[tex]-2(-3)^{2}-5(-3)+4[/tex]

f(-3) =-2(9)+15+4

f(-3)=-18+15+4

f(-3)= -18+19

f(-3)= 1

Answer:

The value of f(–3) for expression  f(a) = –2a² – 5a + 4 is 1 .

Step-by-step explanation:

As given the expression in the question be as follow.

f(a) = –2a² – 5a + 4

Put a = -3 in the above value

f(-3) = –2 × -3 × -3 – 5 × -3 + 4

f(-3) = - 18 + 15+ 4

f(-3) = - 3 + 4

f(-3) = 1

Therefore the value of f(–3) for expression  f(a) = –2a² – 5a + 4 is 1 .